2001
DOI: 10.1081/jdi-100104722
|View full text |Cite
|
Sign up to set email alerts
|

Renal Effects of Cardiac Angiography With Different Low-Osmolar Contrast Media

Abstract: The aim of this study was to evaluate the renal effects of cardiac angiography performed with three low-osmolar contrast media (CM): iopromide (IPR), ioversol (IVR) and ioxaglate (IOX). IPR and IVR are non-ionic CM, IOX is an ionic CM. Different parameters of renal function were determined before and 6, 24, 48, 72 hrs after angiography in 45 patients: 15 patients were examined with IPR, 15 with IVR and 15 with IOX. Glomerular effects--Plasma creatinine increased slightly at the 24th hour after IVR and IOX and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…50 A recent trial that included diabetic patients with preexisting renal disease undergoing coronary and aortic angiography supports the fact that the lowest-osmolality agents, ie, iso-osmolar agents (290 µOsm/kg), provide the best protection from CN. 8 Ionic Content.-One study in humans 51 has confirmed studies of animal models that demonstrated less renal tubular cytotoxicity associated with the use of nonionic contrast media compared with ionic contrast agents. Small clinical trials of low-risk patients undergoing coronary angiography have shown little difference in the risk of CN between the 2 types of medium.…”
Section: Patient-related Risk Factorsmentioning
confidence: 87%
“…50 A recent trial that included diabetic patients with preexisting renal disease undergoing coronary and aortic angiography supports the fact that the lowest-osmolality agents, ie, iso-osmolar agents (290 µOsm/kg), provide the best protection from CN. 8 Ionic Content.-One study in humans 51 has confirmed studies of animal models that demonstrated less renal tubular cytotoxicity associated with the use of nonionic contrast media compared with ionic contrast agents. Small clinical trials of low-risk patients undergoing coronary angiography have shown little difference in the risk of CN between the 2 types of medium.…”
Section: Patient-related Risk Factorsmentioning
confidence: 87%
“…Therefore, besides serum creatinine, according to Fauconneau et al [12] , Goren et al [10] and Rybak et al [4] , we measured the urinary excretion of enzymes and the low-molecular-weight protein ␤ 2M as early markers of damage due to toxic effects of drugs on renal tubular cells, which precedes the clinical impairment in renal function. The clinical relevance of increased excretion of these markers has not been completely elucidated, but data [24][25][26][27][28] indicate that the measurement of urinary excretion of tubular enzymes and the low-molecular-weight protein ␤ 2M may enable the early identifi cation even of mild and transient renal tubular damage, which is not detectable using more conservative criteria, e.g. serum creatinine and CL cr , which only spot signifi cant impairments in glomerular fi ltration rate.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that there is no difference in the cytotoxicity of low-osmolar iomeprol and iso-osmolar iodixanol at equal iodine concentrations in renal proximal tubular cells in vitro, whereby the induced cytotoxicity may consist of a reversible part and an irreversible part. In addition, the viscosity of CM may play a clinically important role in CIN, especially for high-viscous iodixanol (60)(61)(62)(63)(64).…”
Section: Figures 2mentioning
confidence: 99%